Mesopithecus pentelicus from Zhaotong, China, the easternmost representative of a widespread Miocene cercopithecoid species. Issue 146 (September 2020) - Jablonski, Nina G.; Ji, Xueping; Kelley, Jay; Flynn, Lawrence J.; Deng, Chenglong; Su, Denise F.
Abstract: A dentate mandible and proximal femur of Mesopithecus pentelicus Wagner, 1839 are described from the Shuitangba lignite mine in Zhaotong Prefecture, northeastern Yunnan Province, China. The remains were retrieved from sediments just below those that yielded a juvenile Lufengpithecus cranium and are dated at about ∼6.4 Ma. The mandible and proximal femur were found in close proximity and are probably of the same individual. The lower teeth are metrically and morphologically closely comparable with those of confirmed M. pentelicus from Europe, and on this basis, the specimen is assigned to this species. The anatomy of the proximal femur indicates that the Shuitangba Mesopithecus was a semiterrestrial quadruped that engaged in a range of mostly arboreal activities, including walking, climbing, and occasional leaping, with an abducted hip joint. The Shuitangba Mesopithecus is dentally typical for the genus but may have been more arboreal than previously described for M. pentelicus. M. pentelicus is well known from late Miocene (MN 11–12) sites in Europe and southwest Asia. Its estimated average rate of dispersal eastward was relatively slow, although it could have been episodically more rapid. The presence of a colobine, only slightly lower in the same section at Shuitangba that produced Lufengpithecus, is one of the only two well-documented instances of the near or actual co-occurrence of a monkey and ape in the Miocene of Eurasia. At Shuitangba, M. pentelicus occupied a freshwater-margin habitat with beavers, giant otters, swamp rabbits, and many aquatic birds. The presence of M. pentelicus in southwest China near the end of the Miocene further attests to the ecological versatility of a species long recognized as widespread and adaptable. The modern colobines of Asia, some or all of which are probable descendants of Mesopithecus, have gone on to inhabit some of the most highly seasonal and extreme habitats occupied by nonhuman primates.